2015
DOI: 10.1021/acs.jpcc.5b03193
|View full text |Cite
|
Sign up to set email alerts
|

A Nonvacuum Approach for Fabrication of Cu2ZnSnSe4/In2S3 Thin Film Solar Cell and Optoelectronic Characterization

Abstract: Cd-free kesterite-based Cu 2 ZnSnSe 4 (CZTSe)/In 2 S 3 champion solar cell of 5.74% efficiency has been fabricated by chemical spray pyrolysis. In this fabrication route, CZTSe absorber layer was sprayed by using a precursor solution, where metallic salts were dissolved in water-based solvent and subsequently selenized with Se powder at high temperature. In 2 S 3 buffer as an alternative to CdS buffer was also deposited by chemical spray pyrolysis. The device characteristics were studied by measuring dark/ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 58 publications
6
60
0
Order By: Relevance
“…The most likely explanation for the decreasing thickness is that, as S-inclusion increases, the MoSxSe2-x forms a barrier for the diffusion of bigger Se ions, thereby inhibiting further growth of the layer. Additionally, two more modes were observed: a very weak mode at 147 cm −1 that could not be attributed to the kesterite or any secondary phase and a sharper mode at 221 cm −1 that was previously reported for CZGSSe [17]. The latter one is especially interesting since it became the most intense mode when the Figure 2b).…”
Section: The [S]/([s] + [Se]supporting
confidence: 51%
See 2 more Smart Citations
“…The most likely explanation for the decreasing thickness is that, as S-inclusion increases, the MoSxSe2-x forms a barrier for the diffusion of bigger Se ions, thereby inhibiting further growth of the layer. Additionally, two more modes were observed: a very weak mode at 147 cm −1 that could not be attributed to the kesterite or any secondary phase and a sharper mode at 221 cm −1 that was previously reported for CZGSSe [17]. The latter one is especially interesting since it became the most intense mode when the Figure 2b).…”
Section: The [S]/([s] + [Se]supporting
confidence: 51%
“…However, in comparison to the cited publications, all modes were slightly shifted due to the mixed sulfoselenide composition. Additionally, two more modes were observed: a very weak mode at 147 cm −1 that could not be attributed to the kesterite or any secondary phase and a sharper mode at 221 cm −1 that was previously reported for CZGSSe [17]. The latter one is especially interesting since it became the most intense mode when the [S]/([S] + [Se]) ratio was increased to 0.37.…”
Section: The [S]/([s] + [Se]mentioning
confidence: 53%
See 1 more Smart Citation
“…The obtained crossover point is usual for the devices offering high resistive losses. A similar crossover point was reported by Khadka et al [16] for solution processed Cu 2 ZnSnS 4 /In 2 S 3 thin film solar cell. In our fabricated device, a relatively lower FF and the crossover point can be attributed to the higher value of R S , which possibly arises from either back Al/Si contact, or the higher resistivity of AgNWs embedded ITO layer.…”
Section: Current-voltage Analysis Of Solar Cellsupporting
confidence: 86%
“…Since the pioneering report presented by Nakayama et al, many works have been published. Most of them address the preparation of CZTS films by spray pyrolysis, generally obtained from aqueous solutions, alcohol–water mixtures, or from pure organic solvents . Average efficiencies for sprayed kesterite photovoltaic (PV) devices are between 0.55% and 4%, but Larramona et al have reported a 5% efficient pure sulfide CZTS solar cells sprayed from water–ethanol colloidal dispersions and, recently, a 10.6% solar cell device of CZTSSe composition (with Se addition during thermal treatment) .…”
Section: Introductionmentioning
confidence: 99%